Integrating Technology With Human Insight: The Era of Digital Collaboration - Dwiyanto Dwiyanto; Frhendy Aghata (Technologia Journal, 2025)
This study aims to identify an integrative approach between technology and human insight in digital collaboration. The method used is the Systematic Literature Review (SLR), which allows a systematic review of related literature to understand the concepts, models, benefits, and challenges in this integration. This study focuses on three main questions: (1) how technology and human insight are combined in digital collaboration practices, (2) what technologies are commonly used, and (3) what are the benefits and obstacles in this integration. The results of the study show three main patterns of human-technology collaboration: interactive, adaptive, and limited autonomy. In the interactive pattern, humans become decision makers with the support of data-based technology. The adaptive pattern utilizes AI and machine learning that learn from human interactions, but still requires ethical supervision. Meanwhile, the limited autonomy pattern gives decision-making authority to technology in a certain scope with human control. This study emphasizes the importance of the role of human values—such as intuition, empathy, and ethics—in maintaining the effectiveness of digital collaboration. The success of this integration is also influenced by organizational culture and leadership that are adaptive to innovation and a human-centered approach